2017
DOI: 10.1158/1538-7445.sabcs16-p5-15-16
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-15-16: Utilization and outcomes of eribulin in triple negative metastatic breast cancer: Real-world findings

Abstract: Background Triple-negative breast cancer (TNBC) accounts for 10-20% of all breast cancers (BCs) and a significant proportion of all BC deaths. Eribulin is approved for the treatment of metastatic BC (MBC) after treatment with two prior regimens. A pooled analysis of two phase III studies of eribulin in women with TNBC patients found a 26% reduction in the risk of death vs. controls. Treatment patterns of eribulin and clinical outcomes associated with early vs. late use among TNBC patients treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Clinical benefit has been reported in a large 574 unselected patients with MBC, heavily pretreated patients with MBC, elderly patients ≥70 years, heavily pretreated elderly patients with locally recurrent/MBC, metastatic TNBC, ER-positive MBC, hormone-refractory breast cancer, taxane-refractory MBC and in patients with brain metastases. 28,[32][33][34][35][36][37][38][39][40][41] In a retrospective, real-world analysis of 252 patients with metastatic TNBC, it was observed that the estimated realworld OS of 14.7 months for late-line eribulin users was similar to the 13.1 months reported in EMBRACE. 36,42 In a retrospective analysis of observations from study 301, six patients with brain metastases (three each treated with eribulin or capecitabine) were studied as a case series.…”
Section: Real-life Datamentioning
confidence: 70%
See 1 more Smart Citation
“…Clinical benefit has been reported in a large 574 unselected patients with MBC, heavily pretreated patients with MBC, elderly patients ≥70 years, heavily pretreated elderly patients with locally recurrent/MBC, metastatic TNBC, ER-positive MBC, hormone-refractory breast cancer, taxane-refractory MBC and in patients with brain metastases. 28,[32][33][34][35][36][37][38][39][40][41] In a retrospective, real-world analysis of 252 patients with metastatic TNBC, it was observed that the estimated realworld OS of 14.7 months for late-line eribulin users was similar to the 13.1 months reported in EMBRACE. 36,42 In a retrospective analysis of observations from study 301, six patients with brain metastases (three each treated with eribulin or capecitabine) were studied as a case series.…”
Section: Real-life Datamentioning
confidence: 70%
“…28,[32][33][34][35][36][37][38][39][40][41] In a retrospective, real-world analysis of 252 patients with metastatic TNBC, it was observed that the estimated realworld OS of 14.7 months for late-line eribulin users was similar to the 13.1 months reported in EMBRACE. 36,42 In a retrospective analysis of observations from study 301, six patients with brain metastases (three each treated with eribulin or capecitabine) were studied as a case series. 41 All three patients treated with eribulin received six cycles and demonstrated some degree of decrease in the size of their brain lesions during treatment.…”
Section: Real-life Datamentioning
confidence: 70%
“…Observational 'real-world' studies have reported efficacy and tolerability results for eribulin treatment consistent with those reported in clinical trials (Table 2). Clinical benefit has been reported in a large (N = 574) unselected population with MBC [54], heavily pretreated patients with MBC [55], elderly patients ≥70 years old [56], heavily pretreated elderly patients with locally recurrent/MBC [57], metastatic TNBC [58,59], ER-positive MBC [60], hormone-refractory breast cancer [61], taxane-refractory MBC [62] and in patients with brain metastases [63,64]. In a retrospective, real-world study of 252 patients with metastatic TNBC (Table 2), it was noted that the estimated real-world OS of 14.7 months for late-line eribulin users was consistent with the 13.1 months reported in EMBRACE [59,65].…”
Section: Observational Studies Of Eribulinmentioning
confidence: 99%
“…[3][4][5] The design of the pivotal trial indicated that use of eribulin in later lines of therapy in MBC patients is effective, although recent data suggest that the OS benefit with eribulin is greatest in patients who have received fewer lines of chemotherapy. 6,7 However, data also suggest that eribulin may have a role in overcoming the development of resistance to other cytotoxics, through the reversal of chemotherapy-induced epithelial-mesenchymal transition (EMT), suggesting that later line efficacy could be maintained. 8 We conducted this retrospective study to review whether realworld patterns of care in Australian MBC patients treated with eribulin, mirror those published by others.…”
Section: Introductionmentioning
confidence: 99%